Fostering New Language Learning Policies for Adult Immigrants and Refugees in Portugal - Matias, A.R.; Barroso, Margarida (Travailler ensemble – Working Together LESLLA 20th Annual Symposium, 2025)
Based in the analysis of the current Strategic Plan for Portuguese Language Learning (2024-2027, Portugal), the objective of this paper is to discuss the relevance, impact, and apropriateness of language policies for adult immigrants and refugees without or with low literacy. As a first step for inclusion, learning a language is expected to promote access to better chances of acquiring literacy, numeracy, further lifelong learning opportunities, decent jobs, and civic and citizenship participation. However, the policy frameworks for language learning and immigrant inclusion often fail to acknowledge the specific needs of the populations with low literacy or without literacy (Barroso, 2024). In the specific case of Portugal, the need to adjust more efficiently the structure, funding, and implementation of the existing programmes for Portuguese language learning for adult immigrants and refugees, has long been identified since the first implementation of these programmes, more than 20 years ago (Signorello and Matias, 2022; Matias et al. 2016) The new Strategic Plan for Portuguese Language Learning (2024-2027), which is coordinated by the Portuguese Agency for Integration, Migration and Asylum, and results from the consultation with a wide range of public and private entities, aims to address the needs mapped by entities and individuals conceptualizin, implementing, supervising and funding actions in Portuguese language, through a new large scale collaboration at national and local levels. In our paper we question if the aims and measures foreseen in the current plan adress the specific needs of adult immigrants and refugees with little or no literacy, and if they foster greater equality, empowerment, and promotion of social, economic, and political inclusion. In the same vein, we intent to discuss how effective was the consultation process and if the claims of all the actors involved were fully considered.